ANALYSIS OF THE ORGANIZATIONAL MECHANISM OF EFFECTIVE USE OF HUMAN RESOURCES IN SMALL BUSINESS SUBJECTS IN UZBEKISTAN - A. A. Yusupov (European Science Publishing, 2024)
This article analyzes the organizational mechanism of effective use of human resources in small business entities in the conditions of Uzbekistan Analytical opinions were expressed about it. Also, information about the processes of effective use of human resources in the activities of small business entities, the basis of correct assessment and analysis of work performance, and the impact on the development of small business. In addition, the results of the statistical analysis of regions with a high need for employment are highlighted based on analytical approaches.
Keywords: work mechanism, human resources, efficiency, production, human capital, population employment, market economy, labor force.